A novel use of dermoscope in the evaluation of chronic leg ulcer healing progress using low-level laser therapy - Manar N Fayed; Fatma M.A Al-Salam; Abeer M Kamel; Maisa A Abdel Wahab (Wolters Kluwer Medknow Publications, 2020)
Objective Chronic leg ulcers (CLUs) present an economic burden to health care system and significant reductions in quality of life for those affected. Low-level laser therapies (LLLTs) can play a useful role in healing of CLUs. This study aimed to evaluate the efficacy of using LLLT in CLU healing, and we focused on the use of dermoscopy in healing progress follow-up of different types of CLUs regarding some features. Patients and methods This was a case-control study. It included 60 patients recruited from dermatological and vascular outpatient clinics and divided equally into two groups: study group and control group; in each group, there were 10 patients who had arterial ulcer, 10 patients who had diabetic ulcer, and 10 patients who had venous ulcer. The ulcers in the study group were treated by LLLT and the control group received conventional treatment. Pressure ulcer scale for healing and dermoscopic evaluation before and after treatment was done. Results There was a statistically significant difference before and after LLLT, which indicates the progress of healing. The pressure ulcer scale for healing score is decreased in patients who were treated with LLLT compared with patients treated with conventional treatment (P=0.002). Good improvement (≥75%) was seen regarding push healing ratio in the arterial group. Conclusion LLLT is safe, inexpensive, and effective and increases the healing progress of CLUs, which were detected with push score ratio and a novel use of dermoscope.